Relationship between race time and number of accurate shots of the five best biathletes in the 2009/10 world cup in the 10 km race - Rodriguez Padial, R.; Torres, M.; Hernan, O.; Gomez-Lopez, P. J. (Book of Abstracts. 5th International Congress on Science and Skiing, Dec. 14 - 19, 2010, St. Christoph am Arlberg, 2010)
INTRODUCTION: Knowing how to combine fitness with the ability to concentrate and shoot accurately in the firing zone are determinant factors for performance in Biathlon (Sattlecker et al., 2007, 2009). This statistical study analyzes the time and results of the five best biathletes in the different competitions of 2009/10 World Cup classified in the 10 km race.